Diagnosis of the intangible cultural heritage of the Bolivar canton, Manabí, Ecuador communities - Dominguez Sacón, Yanela Nicole (2025)
The research focused on studying the Montubio traditions of the Bolivar canton and their contribution to local socio-cultural and economic development. Its objective was to explore how these traditions influence community identity and cultural tourism. The methodological approach was mixed with an exploratory paradigm, which was applied in three phases: identification and characterization of the traditions, analysis of their socio-cultural and economic contributions, and design of strategies for their sustainability. In the first phase, interviews and documentary reviews were used to identify the most representative practices. In the second phase, the impact of these traditions was evaluated through surveys of 380 inhabitants, demonstrating their value for social cohesion and the local economy. In the second phase, an analysis was conducted on the sociocultural and economic contributions of Montubio traditions. Finally, in the third phase, strategies were designed based on a SWOT analysis to strengthen the transmission of ancestral knowledge and promote cultural tourism. The results showed that Montubio traditions are fundamental to the canton’s identity and economic development, suggesting the need for public policies to support their conservation and promotion.